In-situ coating method of composite positive electrode and all-solid-state battery thereof
By adopting the in-situ coating method of composite positive electrode on the positive electrode of the all-solid state battery, the in-situ coating layer is formed by reacting inorganic solid electrolyte particles with the precursor of the positive electrode active material, solving the problem of slow lithium ion transmission inside the positive electrode and unstable contact of the solid electrolyte, achieving higher battery performance and cycling stability.
Patent Information
- Application Number
- CN202510272991.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-11
AI Technical Summary
The lithium ion transmission inside the positive electrode of the all-solid-state battery is slow and the solid electrolyte contacts the positive electrode active material is unstable, resulting in poor battery performance and poor cycle stability.
Using the in-situ coating method of composite positive electrode, an in-situ coating layer is formed on the surface of the positive electrode active material by reacting inorganic solid electrolyte particles as a lithium donor and a precursor of the positive electrode active material, and a lithium ion conductor is introduced to enhance the contact between the solid electrolyte and the positive electrode active material.
The ion conductivity and high-voltage resistance of the positive electrode are improved, the diffusion of lithium ions between the particles inside the positive electrode is promoted, the polarization of the electrode is reduced, the cycle life of the battery is extended, and the stability is improved.
Smart Images

Figure CN119812288A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to an in-situ coating method for a composite positive electrode and an all-solid-state battery thereof. Background Art
[0002] The flammable organic electrolytes currently used commercially are extremely fluid and volatile, and can easily cause fire and explosion due to thermal runaway of the battery. In pursuit of higher energy density, lithium metal has received widespread attention due to its extremely high theoretical specific capacity. However, in lithium batteries, the use of highly reactive lithium metal as the negative electrode of the organic electrolyte is extremely prone to the formation of dendrites, which may cause short circuits and increase safety risks. To reduce these risks, solid-state electrolytes (SSEs) have become a viable alternative to organic electrolytes, which can effectively prevent fires and inhibit the formation of lithium dendrites when combined with lithium metal.
[0003] However, solid electrolytes do not wet the positive electrode, and the lithium ion transport inside the positive electrode completely relies on the low ionic conductivity of the positive electrode material, which is not conducive to the diffusion of lithium ions between the particles inside the positive electrode. The slow lithium ion transport kinetics inside the positive electrode of solid-state lithium batteries seriously restricts its performance. Therefore, building a lithium ion transport network inside the positive electrode by adding ion conductors is a key issue to consider in designing solid-state batteries with good performance. Usually, inorganic solid electrolyte powder with high ionic conductivity is added to the positive electrode, and the interface between the solid electrolyte and the positive electrode active material is designed to increase the ionic conductivity and reduce the polarization of the electrode.
[0004] In the existing composite positive electrode preparation process, inorganic solid electrolyte powder and positive electrode active material are often only physically mixed, without mutual chemical reaction, and it is difficult to firmly adsorb on the surface of positive electrode material by physical adsorption alone. In addition, during the battery cycle, the volume expansion and contraction of positive electrode materials and side reactions will be encountered, which can easily cause the solid electrolyte coating to fall off, resulting in poor contact between particles inside the positive electrode, hindering the transmission of lithium ions, increasing the internal resistance of the battery, and ultimately leading to rapid decay of battery capacity.
[0005] Therefore, it is necessary to find a simple process to prepare a composite positive electrode with a strong coating layer, construct a continuous and fast lithium ion transmission channel inside the composite positive electrode, improve the compatibility of the electrode with the solid electrolyte, and improve the specific capacity and cycle stability of the solid-state battery. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of slow lithium ion transmission inside the positive electrode of an all-solid-state battery and unstable contact between a solid electrolyte and a positive electrode active material in the background technology, and propose an in-situ coating method for a composite positive electrode and an all-solid-state battery thereof. The present invention uses a solid electrolyte as an in-situ coating of a lithium donor, introduces an ion conductor into the positive electrode and strengthens the contact between the solid electrolyte and the positive electrode active material, improves the ion conductivity and high-voltage resistance of the positive electrode, promotes the release of the capacity of the positive electrode active material, and at the same time, the firm coating interface improves the problem of weak adhesion and easy detachment of the solid electrolyte on the surface of the positive electrode material during the battery cycle, thereby improving the stability of the battery cycle.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A composite positive electrode in-situ coating method and an all-solid-state battery thereof, wherein the composite positive electrode comprises a positive electrode active material and inorganic solid electrolyte particles coated on the positive electrode active material; the positive electrode active material is lithium cobalt oxide (LiCoO 2 ).
[0008] The in-situ coating method of the composite positive electrode comprises the following steps: S1. Dissolve the cobalt source in a mixed solution prepared by 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Dissolve the precipitant in 25 ml of deionized water to obtain solution 2. The molar ratio of the cobalt source to the precipitant is 1:2.
[0009] S2, transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and perform a high temperature reaction at a fixed time and temperature. After the reaction is completed, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven to obtain a cathode material precursor powder.
[0010] S3. Grind and mix the precursor powder prepared in S2 with xA+yB in a molar ratio, and perform solid-phase sintering of the mixture in a muffle furnace using a fixed sintering temperature, sintering time and heating rate. After cooling to room temperature with the furnace, a composite positive electrode powder is obtained, wherein x accounts for 0~10wt.%, y accounts for 90~100wt.%, A is a solid electrolyte powder, and B is a lithium source.
[0011] Furthermore, the cobalt source is cobalt sulfate (CoSO 4 ), cobalt acetate (Co(CH 3 COO 2 ), cobalt nitrate (Co(NO 3 ) 2 ), cobalt chloride (CoCl 2 ) or more; the precipitant is ammonium carbonate ((NH 4 ) 2 CO3 ), sodium carbonate (Na 2 CO 3 ), sodium hydroxide (NaOH) or more.
[0012] As a preferred method, the cobalt source is first placed in deionized water for ultrasonic dissolution, and ethanol is added after the dissolution is complete.
[0013] Furthermore, the hydrothermal reaction temperature is 100~300°C, the reaction time is 8~16h, the oven temperature is 50~100°C, and the drying time is 10~20h.
[0014] Furthermore, the sintering is divided into two steps. The first sintering temperature is 500-600°C, the sintering time is 3-6 hours, and the heating rate is 1-10°C / min; the second sintering temperature is 700-900°C, the sintering time is 10-20 hours, and the heating rate is 1-10°C / min.
[0015] Furthermore, the solid electrolyte powder is one of garnet type, perovskite type, NASICON type or sulfide solid electrolyte, and the garnet type solid electrolyte is Li 7 La 3 Zr 2 O 12 , the perovskite solid electrolyte is Li 3x La 2 / 3-x Ti 3 O 3 , NASICON solid electrolytes are LATP and LAGP, and sulfide solid electrolytes are Li 3 PS 4 , Li 7 P 3 S 11 , Li 10 G 2 S 12 , Li 10 SiP 2 S 12 , Li 6 P 5 S 5 Cl, Li 6 P 5 S 5 Br; lithium source is lithium hydroxide (LiOH), lithium carbonate (Li 2 CO 3 ), lithium nitrate (LiNO 3 ), lithium chloride (LiCl) or more.
[0016] An all-solid-state lithium-ion battery comprises the following steps: Step 1: coating the positive electrode sheet with the composite positive electrode powder prepared in claim 2 Step 2: Select solid electrolyte Step 3: Add the electrolyte dropwise onto the composite cathode and solid electrolyte. The amount added on each side is 1~5uL / cm 2 Step 4: Cover the composite positive electrode on the solid electrolyte, then cover the solid electrolyte on the negative electrode, encapsulate the battery, and obtain a modified all-solid-state lithium-ion battery.
[0017] Furthermore, the solid electrolyte in step 2 is one or more of garnet-type, perovskite-type, NASICON-type or sulfide solid electrolytes, and the garnet-type solid electrolyte is Li 7 La 3 Zr 2 O 12 , the perovskite solid electrolyte is Li 3x La 2 / 3-x Ti 3 O 3 , NASICON solid electrolyte is LATP, LAGP, sulfide solid electrolyte is Li 3 PS 4 , Li 7 P 3 S 11 , Li 10 G 2 S 12 , Li 10 SiP 2 S 12 , Li 6 P 5 S 5 Cl, Li 6 P 5 S 5 Br.
[0018] Furthermore, in step 4, the negative electrode is one of a metal lithium sheet, a metal lithium alloy, graphite, graphene, a silicon-carbon negative electrode, and a lithium-silicon alloy.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides an in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, wherein inorganic solid electrolyte particles are used as lithium donors to react with the precursor of the positive electrode active material to form an in-situ coating layer on the surface of the positive electrode active material, and a lithium ion conductor is introduced into the composite positive electrode, thereby improving the ionic conductivity and high-voltage resistance of the positive electrode, facilitating the diffusion of lithium ions between particles inside the positive electrode, reducing the polarization of the electrode, and promoting the release of the capacity of the positive electrode active material; 2. The in-situ coating method of a composite positive electrode and its all-solid-state battery provided by the present invention change the previous method that solid electrolytes only rely on physical adsorption to be adsorbed on the surface of positive electrode active materials. The solid electrolyte is used as a lithium source to participate in the synthesis of positive electrode materials, which simplifies the coating process and forms a more stable coating interface, strengthens the contact between the solid electrolyte and the positive electrode active material, improves the problem of weak adhesion and easy detachment of the solid electrolyte on the surface of the positive electrode material during the battery cycle, and improves the stability of the battery cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the lithium cobalt oxide positive electrode active material in situ coated with a solid electrolyte prepared in Example 1; Figure 2 The XRD pattern of the lithium cobalt oxide positive electrode active material in situ coated with solid electrolyte prepared in Example 1; Figure 3 Schematic diagram of the structure of an all-solid-state lithium-ion battery, wherein: 1 is a composite positive electrode, 2 is an electrolyte, 3 is a solid electrolyte, and 4 is a negative electrode; Figure 4 The long cycle curve of the all-solid-state lithium-ion battery of Example 1 at 0.1C at a voltage of 3-4.4V; Figure 5 The long cycle curve of the all-solid-state lithium-ion battery of Comparative Example 1 at 0.1C at a voltage of 3-4.4V; DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0022] An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, comprising the following steps: S1, cobalt acetate (Co(CH 3 COO 2 ) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Ammonium carbonate ((NH 4 ) 2 CO 3 ) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt acetate (Co(CH 3 COO 2 ) and ammonium carbonate ((NH 4 ) 2 CO3 ) has a molar ratio of 1:2.
[0023] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 200°C for 12 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a cathode material precursor powder.
[0024] S3, the precursor powder prepared in S2 and 2wt.%Li 7 La 3 Zr 2 O 12 +98wt.%Li 2 CO 3 The mixture was ground and mixed in a molar ratio, and the mixture was heated to 550°C in a muffle furnace at a heating rate of 5°C / min, kept at the constant temperature for 5 hours, and then heated to 850°C at a heating rate of 5°C / min, kept at the constant temperature for 12 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0025] S4, coating the prepared composite positive electrode powder into a positive electrode sheet, selecting Li 7 La 3 Zr 2 O 12 As a solid electrolyte, the electrolyte is dripped onto the surface of the composite positive electrode and the solid electrolyte, with a dripping amount of 5uL / cm on each side. 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, encapsulating the battery, and obtaining a modified all-solid-state lithium-ion battery. Example
[0026] An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, comprising the following steps: S1, cobalt acetate (Co(CH 3 COO 2 ) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Ammonium carbonate ((NH 4 ) 2 CO 3 ) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt acetate (Co(CH 3 COO 2 ) and ammonium carbonate ((NH 4 ) 2 CO 3 ) has a molar ratio of 1:2.
[0027] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 200°C for 12 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a cathode material precursor powder.
[0028] S3, the precursor powder prepared in S2 and 4wt.%Li 7 La 3 Zr 2 O 12 +96wt.%Li 2 CO 3 The mixture was ground and mixed in a molar ratio, and the mixture was heated to 550°C in a muffle furnace at a heating rate of 5°C / min, kept at the constant temperature for 5 hours, and then heated to 850°C at a heating rate of 5°C / min, kept at the constant temperature for 12 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0029] S4, coating the prepared composite positive electrode powder into a positive electrode sheet, selecting Li 7 La 3 Zr 2 O 12 As a solid electrolyte, the electrolyte is dripped onto the surface of the composite positive electrode and the solid electrolyte, with a dripping amount of 5uL / cm on each side. 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, encapsulating the battery, and obtaining a modified all-solid-state lithium-ion battery. Example
[0030] An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, comprising the following steps: S1, cobalt sulfate (CoSO 4 ) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Sodium carbonate (Na 2 CO 3 ) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt sulfate (CoSO 4 ) and sodium carbonate (Na 2 CO 3 ) has a molar ratio of 1:2.
[0031] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 180°C for 10 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 80°C for 10 hours to obtain a cathode material precursor powder.
[0032] S3, the precursor powder prepared in S2 and 1wt.% LATP + 99wt.% LiNO 3 The mixture was ground and mixed in a molar ratio, and the mixture was heated to 500°C in a muffle furnace at a heating rate of 10°C / min, kept at the constant temperature for 6 hours, and then heated to 750°C at a heating rate of 10°C / min, kept at the constant temperature for 15 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0033] S4. Coat the prepared composite positive electrode powder into a positive electrode sheet, select LATP as the solid electrolyte, and drip the electrolyte onto the surface of the composite positive electrode and the solid electrolyte. The dripping amount on each side is 3uL / cm 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, encapsulating the battery, and obtaining a modified all-solid-state lithium-ion battery. Example
[0034] An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, comprising the following steps: S1, cobalt nitrate (Co(NO 3 ) 2 ) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Sodium hydroxide (NaOH) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt nitrate (Co(NO 3 ) 2 ) and sodium hydroxide (NaOH) is 1:2.
[0035] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 300°C for 15 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 100°C for 16 hours to obtain a cathode material precursor powder.
[0036] S3, the precursor powder prepared in S2 and 10wt.%Li 6 P 5 S 5 Cl + 90wt.%LiCl were ground and mixed in a molar ratio, and the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min, kept at the constant temperature for 3 hours, and then heated to 700°C at a heating rate of 5°C / min, kept at the constant temperature for 10 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0037] S4, coating the prepared composite positive electrode powder into a positive electrode sheet, selecting Li 6 P 5 S 5Cl is used as a solid electrolyte. The electrolyte is dripped onto the surface of the composite positive electrode and the solid electrolyte. The dripping amount on each side is 1uL / cm 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, encapsulating the battery, and obtaining a modified all-solid-state lithium-ion battery. Example
[0038] An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, comprising the following steps: S1, cobalt chloride (CoCl 2 ) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Ammonium carbonate ((NH 4 ) 2 CO 3 ) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt chloride (CoCl 2 ) and ammonium carbonate ((NH 4 ) 2 CO 3 ) has a molar ratio of 1:2.
[0039] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 200°C for 12 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a cathode material precursor powder.
[0040] S3, the precursor powder prepared in S2 and 3wt.% LAGP + 97wt.% Li 2 CO 3 The mixture was ground and mixed in a molar ratio, and the mixture was heated to 600°C in a muffle furnace at a heating rate of 5°C / min, kept at the constant temperature for 5 hours, and then heated to 850°C at a heating rate of 5°C / min, kept at the constant temperature for 18 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0041] S4. Coat the prepared composite positive electrode powder into a positive electrode sheet, select LAGP as the solid electrolyte, and drip the electrolyte onto the surface of the composite positive electrode and the solid electrolyte. The dripping amount on each side is 3uL / cm 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, encapsulating the battery, and obtaining a modified all-solid-state lithium-ion battery.
[0042] Comparative Example 1 S1, cobalt acetate (Co(CH 3 COO 2) was dissolved in a mixed solution of 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Ammonium carbonate ((NH 4 ) 2 CO 3 ) was dissolved in 25 ml of deionized water to obtain solution 2. Cobalt acetate (Co(CH 3 COO 2 ) and ammonium carbonate ((NH 4 ) 2 CO 3 ) has a molar ratio of 1:2.
[0043] S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and react at 200°C for 12 hours. After the reaction, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a cathode material precursor powder.
[0044] S3, the precursor powder prepared in S2 and Li 2 CO 3 The mixture was ground and mixed in a molar ratio, and the mixture was heated to 550°C in a muffle furnace at a heating rate of 5°C / min, kept at the constant temperature for 5 hours, and then heated to 850°C at a heating rate of 5°C / min, kept at the constant temperature for 12 hours, and cooled to room temperature in the furnace to obtain a composite positive electrode powder.
[0045] S4, coating the prepared composite positive electrode powder into a positive electrode sheet, selecting Li 7 La 3 Zr 2 O 12 As a solid electrolyte, the electrolyte is dripped onto the surface of the composite positive electrode and the solid electrolyte, with a dripping amount of 5uL / cm on each side. 2 , covering the composite positive electrode on the solid electrolyte, and then covering the solid electrolyte on the lithium negative electrode, packaging the battery, and obtaining an all-solid-state lithium-ion battery with an uncoated positive electrode.
[0046] The all-solid-state batteries prepared in Example 1 and Comparative Example 1 were subjected to a 0.1C charge-discharge cycle test at a voltage of 3-4.4V. The results are as follows: Figure 4 , 5 As shown. Figure 4 , 5It can be seen that the first cycle discharge capacity of Example 1 and Comparative Example 1 is 147.3 and 139.8 mAh / g respectively, and the capacity retention rate after 200 cycles is 86.5% and 77.2% respectively. It can be seen that the present invention uses inorganic solid electrolyte particles as lithium donors to react with the precursor of the positive electrode active material, forms an in-situ coating layer on the surface of the positive electrode active material, introduces a lithium ion conductor into the composite positive electrode, improves the ionic conductivity and high voltage resistance of the positive electrode, is conducive to the diffusion of lithium ions between particles inside the positive electrode, reduces the polarization of the electrode, and promotes the release of the capacity of the positive electrode active material; at the same time, simplifies the coating process, forms a more stable coating interface, strengthens the contact between the solid electrolyte and the positive electrode active material, improves the problem of weak adhesion and easy detachment of the solid electrolyte on the surface of the positive electrode material during the battery cycle, and improves the stability of the battery cycle.
[0047] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments and comparative examples. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of the present invention to be protected is defined by the attached claims and their equivalents.
Claims
1. An in-situ coating method for a composite positive electrode and an all-solid-state battery thereof, characterized in that: The composite positive electrode comprises a positive electrode active material and inorganic solid electrolyte particles coated on the positive electrode active material; the positive electrode active material is lithium cobalt oxide (LiCoO2).
2. The in-situ coating method of the composite positive electrode according to claim 1, characterized in that: The following steps are involved: S1. Dissolve the cobalt source in a mixed solution prepared by 25 ml of deionized water and 12.5 ml of ethanol to obtain solution 1. Dissolve the precipitant in 25 ml of deionized water to obtain solution 2. The molar ratio of the cobalt source to the precipitant is 1:
2. S2. Transfer solution 1 and solution 2 to a 100 mL polytetrafluoroethylene liner to obtain a flocculent compound. Transfer the polytetrafluoroethylene liner to a hydrothermal reactor and perform a high temperature reaction at a fixed time and temperature. After the reaction is completed, wash the prepared precursor with water, filter it, and dry it in a vacuum drying oven to obtain a positive electrode material precursor powder. S3. Grind and mix the precursor powder prepared in S2 with xA+yB in a molar ratio, and solid-phase sinter the mixture in a muffle furnace using a fixed sintering temperature, sintering time and heating rate. After cooling to room temperature with the furnace, a composite positive electrode powder is obtained, in which x accounts for 0~10wt.%, y accounts for 90~100wt.%, A is a solid electrolyte particle, and B is a lithium source.
3. The in-situ coating method of the composite positive electrode according to claim 2, characterized in that: In step S1, the cobalt source is one or more of cobalt sulfate (CoSO4), cobalt acetate (Co(CH3COO)2), cobalt nitrate (Co(NO3)2), and cobalt chloride (CoCl2); the precipitant is one or more of ammonium carbonate ((NH4)2CO3), sodium carbonate (Na2CO3), and sodium hydroxide (NaOH).
4. The in-situ coating method of the composite positive electrode according to claim 2, characterized in that: In the step S1, the cobalt source is first placed in deionized water for ultrasonic dissolution, and ethanol is added after the dissolution is complete.
5. The in-situ coating method of the composite positive electrode according to claim 2, characterized in that: In step S2, the hydrothermal reaction temperature is 100-300° C., the reaction time is 8-16 hours, the oven temperature is 50-100° C., and the drying time is 10-20 hours.
6. The in-situ coating method of the composite positive electrode according to claim 2, characterized in that: In step S3, the sintering is divided into two steps. The first sintering temperature is 500-600°C, the sintering time is 3-6 hours, and the heating rate is 1-10°C / min; the second sintering temperature is 700-900°C, the sintering time is 10-20 hours, and the heating rate is 1-10°C / min.
7. The in-situ coating method of the composite positive electrode according to claim 2, characterized in that: In step S3, the solid electrolyte powder is one of garnet type, perovskite type, NASICON type or sulfide solid electrolyte, and the garnet type solid electrolyte is Li7La3Zr2O 12 , the perovskite solid electrolyte is Li 3x La 2 / 3-x Ti3O3, NASICON type solid electrolytes are LATP, LAGP, sulfide solid electrolytes are Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SiP2S 12 , Li6P5S5Cl, Li6P5S5Br; the lithium source is one or more of lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium nitrate (LiNO3), and lithium chloride (LiCl).
8. An all-solid-state lithium-ion battery, characterized in that: The following steps are involved: Step 1: coating the positive electrode sheet with the composite positive electrode powder prepared in claim 2 Step 2: Select solid electrolyte Step 3: Add the electrolyte dropwise onto the composite cathode and solid electrolyte. The amount added on each side is 1~5uL / cm 2 Step 4: Cover the composite positive electrode on the solid electrolyte, then cover the solid electrolyte on the negative electrode, encapsulate the battery, and obtain a modified all-solid-state lithium-ion battery.
9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The solid electrolyte in step 2 is one or more of garnet type, perovskite type, NASICON type or sulfide solid electrolyte, and the garnet type solid electrolyte is Li7La3Zr2O 12 , the perovskite solid electrolyte is Li 3x La 2 / 3-x Ti3O3, NASICON solid electrolytes are LATP, LAGP, sulfide solid electrolytes are Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SiP2S 12 , Li6P5S5Cl, Li6P5S5Br; in step 4, the negative electrode is one of a metal lithium sheet, a metal lithium alloy, graphite, graphene, a silicon-carbon negative electrode, and a lithium-silicon alloy.
Citation Information
Patent Citations
Preparation method for composite positive electrode material used for solid-state lithium ion battery
CN107017388A
High-mechanical-strength coating-layer-containing positive electrode material, preparation method and application thereof
CN114864940A
Solid electrolyte coated and modified positive electrode material as well as preparation method and application thereof
CN116014142A
Preparation method of solid electrolyte coated lithium ion battery positive electrode material
CN116646523A
Composite positive electrode material, preparation method thereof and lithium ion battery
CN117543021A